Neural Substrates of Poststroke Depression: Current Opinions and Methodology Trends - Pan, Chensheng; Li, Guo; Sun, Wenzhe; Miao, Jinfeng; Qiu, Xiuli; Lan, Yan; Wang, Yanyan; Wang, He; Zhu, Zhou; Zhu, Suiqiang (Frontiers in Neuroscience, 2022)
Poststroke depression (PSD), affecting about one third of stroke survivors, exerts significant impact on patients’ functional outcome and mortality. Great efforts have been made since 1970s to unravel the neuroanatomical substrate and the brain-behavior mechanism of PSD. Thanks to advances in neuroimaging and computational neuroscience in the past two decades, new techniques for uncovering the neural basis of symptoms or behavioral deficits caused by focal brain damage have been emerging. From the time of lesion analysis to the era of brain networks, our knowledge and understanding of the neural substrates for PSD are increasing. Pooled evidence from traditional lesion analysis, univariate or multivariate lesion-symptom mapping, regional structural and functional analysis, direct or indirect connectome analysis and neuromodulation clinical trials for PSD, to some extent, echoes the frontal-limbic theory of depression. The neural substrates of PSD may be used for risk stratification and personalized therapeutic target identification in the future. In this review, we provide an update on the recent advances about the neural basis of PSD with the clinical implications and trends of methodology as the main features of interest.